The Impact of Surgical Safety Guidelines on physicians' and Nurses' Performance and Complications Following Surgeryin Saudi Arabia 2024 - Ibrahim Fallata,; Rashed Madis Almalki,; Afaf Abdullah Farhan Almoqati,; Anood Hussein Hussein Homadi,; Ahlam Mohammed lbrahim Humadi,; Fahad Jaber Mohammed Humedi,; Reem Ayad Alosaimi,; Qamar Mohammad Aolsha,; Khaled Dakheel Allah Al Otaiby,; Khulood Saed Saad Alharbi,; Aminah Mohammed Bakhit Alluqmani, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Surgical care is an integral part of healthcare throughout the world.A significant obstacle facing the health care sector has been surgical safety. Significant advancements have been made in determining the root causes of errors and comprehending the connection between patient outcomes and safety. The study aims: To examines the impact of the implementation of surgical safety guidelines on the performance of physicians and nurses, as well as the incidence of postoperative complications in Saudi Arabia (KSA). Method: A quasi-experimental research design was conducted at the operating room and general surgery department at hospitals in Makkah, KSA. Sample: A convenient sample of 72 of healthcare providersHCPs (physicians and nurses) and 100 patients at the general surgery department. Tools: Four tools were used: I: self-administered questionnaire it included: demographic characteristics of the physicians and nurses and physicians' and nurses' knowledge assessment questionnaire, II: physicians’ and Nurses’ safety practices observational checklist. III: Safety attitude questionnaire, IV: Post-operative Complications Questionnaire: It included demographic characteristics of the patients and post-operative complications. Results: There were high statistically significant differences between physicians’ and Nurses’ mean scores of knowledge post implementation of surgical safety guidelines. All of anesthesia performed surgical safety practices, there were highly statistically significant differences between nurses’ attitudes regarding reporting any safety concerns and working with physicians as a team. As well; there was highly statistically significant reduction of some post-operative complications post implementation of surgical safety guidelines. Conclusion:HCPs’ implementation of surgical safety guidelines had a positive effect on their performance and on reduction of post-operative complications. Recommendations: Surgical safety guidelines should be implemented as part of daily surgical routine and encourages its use to all surgical operations.